2019
DOI: 10.1128/jvi.01539-19
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Mechanism of APOBEC3 Relocalization by Herpesviral Ribonucleotide Reductase Large Subunits

Abstract: An integral part of the antiviral innate immune response is the APOBEC3 family of single-stranded DNA cytosine deaminases, which inhibits virus replication through deamination-dependent and -independent activities. Viruses have evolved mechanisms to counteract these enzymes, such as HIV-1 Vif-mediated formation of a ubiquitin ligase to degrade virus-restrictive APOBEC3 enzymes. A new example is Epstein-Barr virus (EBV) ribonucleotide reductase (RNR)-mediated inhibition of cellular APOBEC3B (A3B). The large sub… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
76
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 79 publications
2
76
0
Order By: Relevance
“…The A3 footprint on EBV is spatially limited to the lagging strands around the lytic replication origins. Interestingly, both EBV and KSHV were recently demonstrated to encode viral proteins capable of inhibiting A3B activity [ 28 , 65 ]. Those viral proteins (EBV BORF2 and KSHV ORF61) are both the large subunit of the ribonucleotide reductase, expressed during lytic replication and providing the precursors necessary for viral DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…The A3 footprint on EBV is spatially limited to the lagging strands around the lytic replication origins. Interestingly, both EBV and KSHV were recently demonstrated to encode viral proteins capable of inhibiting A3B activity [ 28 , 65 ]. Those viral proteins (EBV BORF2 and KSHV ORF61) are both the large subunit of the ribonucleotide reductase, expressed during lytic replication and providing the precursors necessary for viral DNA synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, remnants of vif genelike ORFs have been identified in endogenous lentiviruses (43)(44)(45). In addition, it has recently been reported that herpesviruses encode ribonucleotide reductase large subunits that degrade human A3 proteins (5,46,47) and that the A3 antagonists of Epstein-Barr virus and Kaposi's sarcoma-associated herpesvirus specifically recognize the loop 7 structure of A3B (5). Therefore, A3 antagonists encoded by viruses other than retroviruses may also have exerted selective pressure on the loop 7 structures of A3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, our group has recently uncovered a novel mechanism of HCMV evasion from A3 restriction activity based on the progressive loss of APOBEC hot spots from its genome during evolution [ 10 ]. A3 inactivation as a means to evade host immune surveillance does not seem to be solely restricted to HCMV as other viruses, such as HSV-1 and Kaposi’s sarcoma-associated herpesvirus (KSHV), can delocalize A3 proteins and, in doing so, neutralize their antiviral activity through a conserved ribonucleotide reductase (RNR)-dependent mechanism [ 64 ]. More recently, APOBECs have been involved in SARS-CoV-2 RNA editing [ 65 ].…”
Section: Apobec Genes Vs Hpvs: Restriction Factors or Dna Editorsmentioning
confidence: 99%